Influence of PdO content and pathway of its formation on methane combustion activity - Choudhary, Tushar V.; Banerjee, S.; Choudhary, Vasant R. (Catalysis Communications, 2005)
The methane oxidation reaction is known to induce changes in the surface structure and composition of Pd catalysts; making it extremely arduous to relate the methane oxidation activity to specific catalyst properties by conventional methods (continuous flow reactor studies). To circumvent this, methodical pulse reactor studies have been undertaken to obtain correlations between the initial methane combustion activity and the catalyst properties (Pd-0/PdO content and path of PdO formation). While the initial methane combustion activity (at 160-280 degreesC) continuously increased with increasing PdO concentration (0-100%) in the catalyst, it continuously decreased with increasing Pddegrees content (0-100%). Controlled studies were undertaken to obtain catalysts with identical PdO content by two pathways: (i) by controlled partial oxidization of Pd-0/Al2O3 and (ii) by controlled partial reduction of PdO/Al2O3. Interestingly, for a given PdO content, the catalysts obtained by partial oxidation of Pd-0/Al2O3 showed a significantly superior performance to the catalyst obtained by partial reduction of PdO/Al2O3 for all the temperatures investigated. These studies unambiguously show that along with the relative concentration of PdO, the PdO formation pathway is also critical in deciding the methane combustion activity of the catalyst. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Methane combustion; Oxidation; partially oxidized Pd-0/Al2O3; partially reduced PdO/Al2O3; Pd-0/Al2O3; PdO/Al2O3; pulse reaction of methane

Direct oxidation of H-2 to H2O2 over PdO/Al2O3 catalysts in aqueous acidic medium: influence on H2O2 formation of Pd loading, calcination temperature and reduction of catalyst and presence of halide anions - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the Pd loading (0.2-10 wt%), calcination temperature (400-900 degrees C) and reduction of PdO/Al2O3 on its performance in the H-2-to-H2O2 oxidation (with H-2/O-2 = 1:1) in an aqueous 0.1 M H3PO4 medium, in the absence and presence of different halide anions, under ambient conditions have been investigated. The effect of calcination temperature on the H2O2 formation varied depending upon the Pd loading. The influence of the different halide anions was found to depend strongly on the nature of halide anion (F-, Cl-, Br- or I-) and the oxidation state of Pd and its loading in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: halide catalyst promoters; Hydrogen peroxide; oxidation of H-2 to H2O2; Pd/Al2O3; PdO/Al2O3